59‐1: FFS‐Based Privacy LCD with High Contrast and Transmittance. Issue 1 (25th September 2020) - Murata, Koji; Yoshida, Hidefumi; Hanaoka, Kazutaka; Shimada, Shinji
Abstract : We have developed an FFS‐based LCD that can be switched between two display modes: 1) wide view mode with high contrast ratio and 2) narrow view mode enabling privacy. By combining the new LCD configuration with Soft Veil View technology, our 5.3‐inch prototype has successfully enabled: 1) enhanced optical properties and 2) privacy mode with a larger off‐axis area that prevents unauthorized image viewing.